2009
DOI: 10.1097/mcg.0b013e3181a4e772
|View full text |Cite
|
Sign up to set email alerts
|

Association of SPINK1 Gene Mutation and CFTR Gene Polymorphisms in Patients With Pancreas Divisum Presenting With Idiopathic Pancreatitis

Abstract: Patients with pancreas divisum presenting with idiopathic pancreatitis had a higher frequency of SPINK1 gene mutation compared with healthy controls, which might be responsible as the sole-factor or a co-factor in causing pancreatitis in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 30 publications
3
35
1
Order By: Relevance
“…Although our study results demonstrate that normal pancreatic duct variants and variants of pancreas divisum are not associated with signs of CP or a restriction of pancreatic exocrine function, we cannot rule out that additional genetic factors such as mutations in the SPINK-1 gene or CFTR gene might infer susceptibility for chronic pancreatitis [33][34][35][36][37][38].…”
Section: Discussioncontrasting
confidence: 53%
“…Although our study results demonstrate that normal pancreatic duct variants and variants of pancreas divisum are not associated with signs of CP or a restriction of pancreatic exocrine function, we cannot rule out that additional genetic factors such as mutations in the SPINK-1 gene or CFTR gene might infer susceptibility for chronic pancreatitis [33][34][35][36][37][38].…”
Section: Discussioncontrasting
confidence: 53%
“…In a case–control design, 113 patients with idiopathic CP, 42 patients with alcoholic CP, seven with hereditary pancreatitis, eight with familial pancreatitis and 100 healthy controls were studied for mutations in three genes: that is, cationic trypsinogen ( PRSS1 ), CFTR and SPINK1 genes as described earlier 16. We included voluntary healthy controls from among the hospital staff and relatives of the patients attending the outpatient department.…”
Section: Methodology For Different Objectivesmentioning
confidence: 99%
“…We have shown that SPINK1 (pancreatic secretory trypsin inhibitor) gene mutations were present in 40% of patients with IRAP and PD. 45 In addition, many CFTR (cystic fibrosis transmembrane regulator) gene polymorphisms were also found in them. These were similar to the mutations seen in patients with IRAP without PD and those with CP.…”
Section: Pancreas Divisum (Pd)mentioning
confidence: 99%
“…The reason why many patients with PD and IRAP may not respond well to minor papilla sphincterotomy is that genetic mutations might be more important in causing pancreatitis in such patients. 45,97 There is a significant role of antioxidants in reducing relapses in patients with early CP presenting with recurrent pain.…”
Section: Phase II Investigationsmentioning
confidence: 99%